2016
DOI: 10.1007/s00125-016-4077-2
|View full text |Cite
|
Sign up to set email alerts
|

The type 2 diabetes presumed causal variant within TCF7L2 resides in an element that controls the expression of ACSL5

Abstract: Aims/hypothesis One of the most strongly associated type 2 diabetes loci reported to date resides within the TCF7L2 gene. Previous studies point to the T allele of rs7903146 in intron 3 as the causal variant at this locus. We aimed to identify the actual gene(s) under the influence of this variant. Methods Using clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein-9 nuclease, we generated a 1.4 kb deletion of the genomic region harbouring rs7903146 in the HCT116 cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 22 publications
4
57
1
Order By: Relevance
“…Reported whole-body Acsl5 knockout mice show a consistent reduction in blood glucose levels [8,9] and improvements in insulin sensitivity [8]. In line with this, the study by Xia et al shows lower ACSL5 expression in the non-risk C allele compared with the type 2 diabetes risk-increasing T allele [6].These findings are also in agreement with previous observations in human islets, which demonstrate that the T allele confers greater enhancer activity at rs7903146 [10].…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Reported whole-body Acsl5 knockout mice show a consistent reduction in blood glucose levels [8,9] and improvements in insulin sensitivity [8]. In line with this, the study by Xia et al shows lower ACSL5 expression in the non-risk C allele compared with the type 2 diabetes risk-increasing T allele [6].These findings are also in agreement with previous observations in human islets, which demonstrate that the T allele confers greater enhancer activity at rs7903146 [10].…”
supporting
confidence: 85%
“…In the current issue of Diabetologia, Xia and colleagues [6] perform a series of state-of-the-art experiments to provide an alternative effector gene for the TCF7L2 locus, ACSL5. The authors deleted a 1.4 kb genomic region containing the variants most strongly associated with type 2 diabetes, in human intestinal epithelial cell lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported that better maintenance in glucose levels [20,21] and improvement in insulin sensitivity [20] in the whole-body ACSL5 knockout mice. Xia et al [22] found that a causal variant within TCF7L2 resides in an element that controls the expression of ACSL5 and speculated that TCF7L2 regulates ACSL5 expression. Given the correlation between ACSL5 and insulin sensitivity, inhibiting ACSL5 enzyme activity to treat T2DM could be promising.…”
Section: Genetic Mutation In Tcf7l2mentioning
confidence: 99%
“…Discovered in 2006 as a gene containing a common intronic variant with a relatively strong effect on type 2 diabetes risk [43], it was not until 2010 that fine-mapping and functional studies conclusively proved that the rs7903146 variant was causal in influencing TCF7L2 expression in islets [44], although a recent report suggests that it may act via another effector transcript [45]. Physiological studies in the DPP first demonstrated that this type 2 diabetes-associated variant diminishes beta cell function [46], but the precise molecular mechanisms by which the protein encoded by TCF7L2 (transcription factor 7-like 2 [TCF7L2]) does so have proven elusive.…”
Section: Slc22a1mentioning
confidence: 99%